1999
DOI: 10.3923/pjbs.2000.188.190
|View full text |Cite
|
Sign up to set email alerts
|

Okra Leaf Cotton, its Commercial Utilization in Sindh

Abstract: Studies were under taken to assess the yield, earliness and insect pest resistance of some newly developed okra leaf strains compared with normal leaf commercial varieties CRIS-9 and NIAB-78. Accordingly, almost all the okra leaf mutants yielded better than NIAB-78. Out of nine okra leaf strains, throb were better yields, two equally good and four gave low yield than CRIS-9 the second check variety. Highest yielding okra leaf strain produced 27 and 35 percent higher yield than CRIS-9 and NIAB-78 respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It has been reported that population buildup of sucking insect pests on cotton with okra leaf trait is comparatively low due to its open canopy (Chu et al, 2000;Soomro et al, 2000;Ahmad et al, 2005;Din et al, 2016). The objective of present research was to explore the potential of Bt cotton with okra leaf trait for resistance against sucking insect pests and bollworms.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that population buildup of sucking insect pests on cotton with okra leaf trait is comparatively low due to its open canopy (Chu et al, 2000;Soomro et al, 2000;Ahmad et al, 2005;Din et al, 2016). The objective of present research was to explore the potential of Bt cotton with okra leaf trait for resistance against sucking insect pests and bollworms.…”
Section: Introductionmentioning
confidence: 99%